Faith in frames: unveiling therapeutic narratives in religion-related cinema through computational analysis - Xue, Bai; Wang, Zhongrui; Liu, Yuqing; Song, Yao (Frontiers in Public Health, 2024)
This study explores the emotional impact of religion-related films through a "cinematherapy" lens. Utilizing facial recognition with YOLOv5 object detection, we analyzed emotional patterns in a curated selection of religion-related films compared to a broader sample of acclaimed movies. Our analysis revealed distinct emotional trajectories. Religion-related films exhibited a subtler range of emotions compared to the broader film spectrum. This potentially creates a safe space for contemplation, aligning with the profound themes these films often grapple with. The observed emotional arc mirrored spiritual journeys depicted in the films. Films started with a low point (separation), transitioned through challenges, and culminated in a peak representing spiritual transformation. These findings suggest promise for the therapeutic application of religion-related films. The muted emotional expression creates a safe space for self-reflection, allowing viewers to connect with characters' struggles and explore their own values in the face of complex religious ideas. This emotional engagement may contribute to therapeutic goals like introspection and personal growth. Unveiling the unique emotional power of religion-related films, this study paves the way for further research on their potential as therapeutic tools.This study explores the emotional impact of religion-related films through a "cinematherapy" lens. We analyzed emotional patterns in a curated selection of religion-related films compared to a broader sample of acclaimed movies. Our analysis revealed distinct emotional trajectories. Religion-related films exhibited a subtler range of emotions compared to the broader film spectrum. This potentially creates a safe space for contemplation, aligning with the profound themes these films often grapple with. Interestingly, the observed emotional arc mirrored spiritual journeys depicted in the films. Films started with a low point (separation), transitioned through challenges, and culminated in a peak representing spiritual transformation. These findings suggest promise for the therapeutic application of religion-related films. The muted emotional expression creates a safe space for self-reflection, allowing viewers to connect with characters' struggles and explore their own values in the face of complex religious ideas. This emotional engagement may contribute to therapeutic goals like introspection and personal growth.